A NewSpeed Power Area and Accuracy (SPAA) Aware Cordic Processing Unit By Vedic Mathematics For The Application of Computer Vision - et. al., Nitesh Kumar Sharma, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
we are living in the era of fast processing applications like 3D, 5G, 9D. These types of application need a processing unit which have separate arithmetic unit & separate trigonometric unit which is well known as CORDIC processing unit. As we know Graphics processing unit is the brain of any graphics systems now a days there is Gaming specific systems are available which require ultra-high-speed GPU on those GPU there is separate trigonometric calculation processing unit is there which is called CORDIC. So, in this paper basically we proposed a novel architecture of CORDIC unit which is able to give the output in very less time. In this paper we also try to do the justice with the speed power area and accuracy Metrix.